2016
DOI: 10.1016/j.mmcr.2016.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Successful therapy of Candida pulcherrima fungemia in a premature newborn with liposomal amphotericin B and micafungin

Abstract: New Candida species may cause bloodstream infections challenging current therapeutic approaches because of unpredictable susceptibility and virulence. In the present report, we describe a fungemia case due to Candida pulcherrima in a premature neonate. After full in vitro diagnostic workup, the neonate was successfully treated with liposomal amphotericin B and micafungin achieving rapid fungal eradication from blood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…Liposomal amphotericin B is also recommended, not as a first line, with similar efficacy as micafungin. A successful outcome was observed with liposomal amphotericin B plus micafungin in a pre-term infant with C. pulcherrima fungemia and in an oncology patient suffering C. guillermondii infection [ 35 , 36 ]. Favorable results were reported for C. krusei fungemia treated with amphotericin B plus caspofungin [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Liposomal amphotericin B is also recommended, not as a first line, with similar efficacy as micafungin. A successful outcome was observed with liposomal amphotericin B plus micafungin in a pre-term infant with C. pulcherrima fungemia and in an oncology patient suffering C. guillermondii infection [ 35 , 36 ]. Favorable results were reported for C. krusei fungemia treated with amphotericin B plus caspofungin [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical evidence regarding the combination of amphotericin B with echinocandins for invasive candidiasis is scarce and mostly published as case reports. Mpakosi et al reported the successful treatment with liposomal amphotericin B and micafungin of a preterm infant with Candida (Metschnikowia) pulcherrima fungaemia [ 36 ]. This rare species is, along with C. auris , part of the Metschnikowiaceae family.…”
Section: Discussionmentioning
confidence: 99%